La gestión del talento humano y la productividad de la Empresa Tecnimadera, ubicada en la Ciudad de Baños de Agua Santa, Tungurahua – Ecuador. - López Orozco, Tatiana Paola (2022)
The objective of this research was to determine the relationship between the management of human talent and labor productivity to improve the existing processes in the Tecnimadera company in the city of Baños de Agua Santa. For this, an instrument consisting of a questionnaire that consisted of a total of 20 items was validated, distributed in 10 for each study variable, which were the management of human talent and the other productivity, the Cronbach's alpha found was of 0.747., which is good. The level of relationship that exists between the two variables: management of human talent and productivity was determined, by means of the deductive scientific research method with a non-experimental design of a correlational descriptive level where the sample was constituted by the total of the workers of the company. The management of human talent is related to productivity in the company with a Spearman Rho correlation of 0.667 and, therefore, it is recommended to manage individual and group knowledge, since it is necessary for the development of new experiences, skills, and knowledge, through the creation of training programs. Keywords: human talent management, productivity, company.